Global cerebrospinal fluid as a zero‐reference regularization for brain quantitative susceptibility mapping - Dimov, Alexey V.; Nguyen, Thanh D.; Spincemaille, Pascal; Sweeney, Elizabeth M.; Zinger, Nicole; Kovanlikaya, Ilhami; Kopell, Brian H.; Gauthier, Susan A.; Wang, Yi (Journal of neuroimaging, 2022)
Background and Purpose The objective ofthis study was to demonstrate a global cerebrospinal fluid (CSF) method for a consistent and automated zero referencing of brain quantitative susceptibility mapping (QSM). Methods Whole brain CSF mask was automatically segmented by thresholding the gradient echo transverse relaxation (R2∗) map, and regularization was employed to enforce uniform susceptibility distribution within the CSF volume in the field‐to‐susceptibility inversion. This global CSF regularization method was compared with a prior ventricular CSF regularization. Both reconstruction methods were compared in a repeatability study of 12 healthy subjects using t‐test on susceptibility measurements, and in patient studies of 17 multiple sclerosis (MS) and 10 Parkinson's disease (PD) patients using Wilcoxon rank‐sum test on radiological scores. Results In scan‐rescan experiments, global CSF regularization provided more consistent CSF volume as well as higher repeatability of QSM measurements than ventricular CSF regularization with a smaller bias: –2.7 parts per billion (ppb) versus –0.13 ppb (t‐test p<0.05) and a narrower 95% limits of agreement: [−7.25, 6.99] ppb versus [−16.60, 11.19 ppb] (f‐test p<0.05). In PD and MS patients, global CSF regularization reduced smoothly varying shadow artifacts and significantly improved the QSM quality score (p<0.001). Conclusions The proposed whole brain CSF method for QSM zero referencing improves repeatability and image quality of brain QSM compared to the ventricular CSF method.